PENGARUH TUNJANGAN KERJA STATIS DAN DINAMIS DAN PENILAIAN SASARAN KERJA PEGAWAI (SKP) TERHADAP KINERJA PEJABAT PELAKSANA TEKNIS KEGIATAN (PPTK) DI SEKRETARIAT DAERAH KOTA TANGERANG - Sukamto , MD; Warsito, Agus (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2021)
The purpose of this study is to determine the effect of Allowances Work Static and Dynamic and Assessment Targets Employee Work (SKP) on the Performance Executive Officer Technical Activities (PPTK) in the Regional Secretariat Tangerang, where the variables under study consists of independent variables (X1) allowances static work and dynamic, targeted employee (X2) and performance PPTK (Y) as the dependent variable. Quantitative methods with this kind of associative become the means used to identify the influence of the independent variables and the dependent variable in this study, where the survey was conducted on 50 employees at the Environment Secretariat PPTK Tangerang City Regional are taken randomly. Based on the research results can be obtained information that the employment benefits of static and dynamic (X1) positive effect of increasing the performance of PPTK (Y) in the Regional Secretariat Tangerang with a degree of influence being as well as with the target employee (X2) can have a positive influence on the performance PPTK within the Regional Secretariat Tangerang. Besides static and dynamic employment benefits (X1) and the target employee (X2) simultaneously positive effect on performance improvement PPTK (Y). This is evident from the results of calculation of correlation coefficient = 0.634 ryX1X2 that produce value determination coefficient of 0.4020, which means that the variation of the variable Y can be explained by X1 and X2 amounted to 40.20% and it is predicted through linear regression line equation y = 15.608 + 0.842 X1 + 0,544X2. Static and dynamic benefits should consider the adequacy of the needs of employees, compliance ranks and classes of employees, and benefit allowances for pegawaih it is worth noting because it can affect the performance of the PPTK located inside the Regional Secretariat Tangerang. Target employee must consider several factors such as the execution of the duties of office pendukunganya covering employee understanding of the duties and functions as well as the main tasks and functions, employee behaviors that include service orientation, integrity, commitment, discipline, and kerjsama employees to do the job. It is worth noting because the results can influence the performance terhadak PPTK in the Tangerang City Regional Secretariat.